- #1

- 92

- 4

In the derivation on Wikipedia, it says the following

## \frac{dv}{dt}=\frac{dv}{dx}\frac{dx}{dt}=\frac{dv}{dx}v = \frac{d}{dx}[\frac{v^2}{2}] ##

How do they go from the second to last to last equation? I've been trying to understand, but I think I'm just looking over something incredibly simple.

## \frac{dv}{dt}=\frac{dv}{dx}\frac{dx}{dt}=\frac{dv}{dx}v = \frac{d}{dx}[\frac{v^2}{2}] ##

How do they go from the second to last to last equation? I've been trying to understand, but I think I'm just looking over something incredibly simple.

Last edited: